Exergy analysis and Exergetic sustainability index of package boiler - Bustan, Muhammad Djoni; Haryati, Sri; Serigianto, Serigianto (Akademisi dan Saintis Indonesia (ASASI), 2024)
Energy is one of the basic human needs. Economic growth and population growth in a country which continues to increase is directly proportional to the growth in energy needs required by society. Indonesia is the largest energy user in Southeast Asia, namely more than 36% of Southeast Asia's primary energy use. Utilization of the energy used will reduce the increase in production costs for an industry. The use of energy is better known as energy conservation. Energy and exergy analysis based on the first and second laws of thermodynamics is used to analyze the thermal system of industrial units. This can be applied to equipment units in the fertilizer industry to identify sources of inefficiency, determine their location and the amount of exergy destruction that occur. To reduce exergy destruction, this can be done by modifying the operating conditions of the package boiler. The results show that 94.3% of the total exergy destruction from the boiler package is obtained from the evaporator component with a value of 2.7 x 108 kJ/hr Modification of the operating conditions of the evaporator is carried out by reducing Boiler Feed Water (BFW) inlet temperature with T 100C (196 – 116 oC). The decrease BFW temperature will increase the amount of required latent heat and reduce the convection heat that will be carried by the flue gas to generate superheated steam. Optimization of the BFW temperature is performed be calculating the flue gas temperature and exergoeconomic analysis. Exergoeconomic analysis is performed by calculating the cost rate of exergy destruction (ĊD,k) and exergoeconomic factor (fk). The results obtained were that the temperature was optimum of BFW is at 161°C which resulted the reduction of exergy destruction of 6,2x106 kJ/hr and resulting difference cost losses based on actual data (196 oC) of Rp 1,370,354,743/hr. Exergetic Sustainability Index (ESI) used to demonstrate how reducing a system's environmental impact can be achieved by reducing its exergy consumption (destruction and losses) or increasing its exergetic efficiency. In this research, ESI Value was achieved at 0.918.